Elites políticas em Caraguatatuba (1970-2000) - Souza, Samuel Candido de (Universidade Federal de São Carlos, 2010)
In view of the process of administrative decentralization promoted by the federal government, especially after the 1988 Constitution, the local level becomes crucial regarding the implementation of public policies and the promotion of economic development. Thus increases the importance of local political elites who will be responsible for more significant policy decisions with immediate impact on the citizen s lives. This research analyzes the process of recruitment of political elites in Caraguatatuba County during the period corresponding to the years 1970 to 2000. We attempt to correlate changes in the social composition of the elite to the social and economic transformations occurring in the city during this period as well as the institutional transformations occurred in the country. We emphasize the processes of political integration of social agents concerning to the mechanisms leading to conversion of social resources into political capital for the establishment of elites at the local level.
Keywords: Elites políticas; Poder local; Capital social; Mudanças sócio-econômicas; Recursos políticos; Political elites; Local government; Political resources; Socioeconomic changes; CIENCIAS HUMANAS::CIENCIA POLITICA